Explorando gamificação no ensino de teste de software - Jesus, Gabriela Martins de (2019)
Context: Testing is a fundamental activity in the development process, and aims at revealing faults. Despite its importance, the time devoted to testing education has not been enough, resulting in the lack of trained professionals. Other problems faced are misalignment between what is taught and what is applied in the industry, inefficiency of lectures, unattractive classes, and lack of practical activities. Aiming at solving them, alternative educational approaches have been investigated, such as serious games, flipped classroom, and gamification. Gamification, in turn, is a promising trend that uses game elements in real-world contexts in order to increase people’s motivation and engagement in tasks that require external stimuli, especially in educational contexts.Objectives: Contributing to software testing education by investigating whether the use of gamification in this context increases students’ motivation and performance when compared to the conventional approach.Method: A systematic literature mapping was carried out aiming at characterizing how gamification has been explored in the software testing context. In addition, some of the problems faced by testing education were identified through an ad-hoc search. Then, a gamified approach was developed, and a platform was implemented containing the created approach. Experimental sessions were run, and the collected results were analyzed. Results: In general, it is not possible to state that the motivation and performance of students who learned through the gamified approach is higher than those who learned through the conventional approach, given that, for each experimental group, the results were different when compared with the control group. However, the experience of having used this alternative approach is considered positive, as it provided a more enjoyable and funny environment, both from the researcher’s and students’ point of view.